2015
DOI: 10.1093/aobpla/plv146
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics of drought-induced trans-generational plasticity: consequences for range limit development

Abstract: Offspring phenotypes may be altered by environments that their parents lived in. These environmentally-induced trans-generational effects may be mediated by epigenetic mechanisms such as DNA methylation. Little is known about the role of such epigenetic effects in evolution; however, it is expected to facilitate evolution. To expand geographic range, it is thought that most species would have to adapt via evolution by natural selection to stressful environments beyond range boundaries. Contrary to expectations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…These adaptive phenotypes may be expressed constitutively or may be induced by an environmental cue that predicts a change in water availability later in the life of the organism. Increasingly, experimental studies show that the parental soil moisture regime can also adaptively influence the development of progeny (Alsdurf, Anderson, & Siemens, ; Alsdurf, Ripley, Matzner, & Siemens, ), providing a third route by which plants can fine tune the phenotypes of their offspring to local soil moisture levels. For instance, in Massachusetts genotypes of the annual plant Polygonum persicaria , offspring of drought‐stressed parents make more extensive root systems and deploy them faster in response to drought as compared to offspring of well‐watered parents.…”
Section: Discussionmentioning
confidence: 99%
“…These adaptive phenotypes may be expressed constitutively or may be induced by an environmental cue that predicts a change in water availability later in the life of the organism. Increasingly, experimental studies show that the parental soil moisture regime can also adaptively influence the development of progeny (Alsdurf, Anderson, & Siemens, ; Alsdurf, Ripley, Matzner, & Siemens, ), providing a third route by which plants can fine tune the phenotypes of their offspring to local soil moisture levels. For instance, in Massachusetts genotypes of the annual plant Polygonum persicaria , offspring of drought‐stressed parents make more extensive root systems and deploy them faster in response to drought as compared to offspring of well‐watered parents.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the perennial plant Boechera stricta, Alsdurf & colleagues [33] found that parental drought caused changes in DNA methylation that correlated with increased drought-tolerance in offspring. These transgenerational changes also correlated with decreased production of defensive chemicals in offspring, thus implicating epigenetic inheritance in an ecologically meaningful trade-off between offspring tolerances to different stresses.…”
Section: Discussion (A) Dna Methylation Mediates Adaptive Transgeneramentioning
confidence: 99%
“…Likewise, together with the biological variability in the methylation level of the samples, it must be taken into account that although the MSAP technique is quite reproducible, there may be technical errors that cause a fragment to be absent or present [ 118 ]. In this sense, some authors replicate independently some samples to be studied by the MSAP technique; they determine an error rate per fragment and only consider to analyze those fragments with error rates lower than a threshold value [ 89 , 119 , 120 ]. These authors report error rates ranging from 2% to 10%.…”
Section: Statistical Methods For Msap Analysis In Plant Conservatimentioning
confidence: 99%